2023
DOI: 10.1038/s41598-023-27599-z
|View full text |Cite
|
Sign up to set email alerts
|

Device simulations with A U-Net model predicting physical quantities in two-dimensional landscapes

Abstract: Although Technology Computer-Aided Design (TCAD) simulation has paved a successful and efficient way to significantly reduce the cost of experiments under the device design, it still encounters many challenges as the semiconductor industry goes through rapid development in recent years, i.e. Complex 3D device structures, power devices. Recently, although machine learning has been proposed to enable the simulation acceleration and inverse‑design of devices, which can quickly and accurately predict device perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Still, the applications of CNN-based approach are limited in the semiconductor research. Recently, one study reported that the pixels of the two-dimensional landscape of low-voltage Si devices could be modeled by a CNN with a U-Net architecture 26 . Note that the advantage of using a U-Net CNN is that, in general, U-Net CNN requires only few images to have a relatively good results 23 – 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, the applications of CNN-based approach are limited in the semiconductor research. Recently, one study reported that the pixels of the two-dimensional landscape of low-voltage Si devices could be modeled by a CNN with a U-Net architecture 26 . Note that the advantage of using a U-Net CNN is that, in general, U-Net CNN requires only few images to have a relatively good results 23 – 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the expansive pathway unites feature and spatial information by employing up-convolutions and merging them with high-resolution features obtained from the contracting path through concatenation. However, this work 26 is limited to the dimensional variation with only considering the impact of on-state voltage that directly applied at the surface of the semiconductor with simplified symmetric device design that is not practical for the real device fabrication, which results from the relative compact and shallow network constructed by only 4 layers of contracting path and the expanding path. Furthermore, the impacts of the external dimensional variations, e.g., field plate variations on top of the semiconductor, on the potential distribution inside the semiconductor are not discussed 26 , which is more practical for the consideration of the semiconductor design.…”
Section: Introductionmentioning
confidence: 99%